Tingkat Kepatuhan Minum Obat Pasien Tuberculosis Rawat Jalan di RSUD Soehadi Pridjonegoro Kabupaten Sragen - Khotimatul Khusna; Syahida Ulya Amalina; Fadilah Qonitah (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Tuberculosis (TB) is a contagious infectious disease that is still a global health problem, with Indonesia as one of the countries with the highest cases. The success of TB therapy is highly dependent on patient compliance in taking anti-tuberculosis drugs (OAT) regularly. Factors that influence the level of medication compliance in pulmonary TB patients are gender, age, occupation, education, family support, and drug side effects. This study aims to determine the level of compliance of patients taking outpatient pulmonary TB medication at Soehadi Pridjonegoro Regional Hospital, Sragen Regency. This research uses a descriptive method with a quantitative approach. The sample used in the research was 97 respondents. Sampling using techniques purposive sampling. Data was taken using a validated questionnaire created based on the MARS questionnaire (Medication Adherence Rating Scale). The results of the study showed that patients with a high level of compliance were 65 respondents with a percentage of (67%) and moderate compliance was 32 respondents with a percentage of (33%). The conclusion of this research is that patients take outpatient pulmonary TB medication at Soehadi Pridjonegoro Hospital, Sragen Regency with a high level of compliance (67%) with a total of 65 respondents.